Characterization of a putative sensory [FeFe]-hydrogenase provides new insight into the role of the active site architecture. Issue 47 (28th September 2020) - Land, Henrik; Sekretareva, Alina; Huang, Ping; Redman, Holly J.; Németh, Brigitta; Polidori, Nakia; Mészáros, Lívia S.; Senger, Moritz; Stripp, Sven T.; Berggren, Gustav
Abstract : Characterization of a group D putative sensory [FeFe]-hydrogenase reveals how the active site can be tuned to decrease CO inhibition and increase stability of a reduced H-cluster while retaining the ability to catalyze H + /H2 interconversion. Abstract : [FeFe]-hydrogenases are known for their high rates of hydrogen turnover, and are intensively studied in the context of biotechnological applications. Evolution has generated a plethora of different subclasses with widely different characteristics. The M2e subclass is phylogenetically distinct from previously characterized members of this enzyme family and its biological role is unknown. It features significant differences in domain- and active site architecture, and is most closely related to the putative sensory [FeFe]-hydrogenases. Here we report the first comprehensive biochemical and spectroscopical characterization of an M2e enzyme, derived from Thermoanaerobacter mathranii . As compared to other [FeFe]-hydrogenases characterized to-date, this enzyme displays an increased H2 affinity, higher activation enthalpies for H + /H2 interconversion, and unusual reactivity towards known hydrogenase inhibitors. These properties are related to differences in active site architecture between the M2e [FeFe]-hydrogenase and "prototypical" [FeFe]-hydrogenases. Thus, this study provides new insight into the role of this subclass in hydrogen metabolism and the influence of the active site pocket on the chemistry of the H-cluster.